Oral Health Knowledge, Attitude and Behaviour of Indonesian Dental Students in East Java Province, Indonesia - Hariyani, Ninuk; Safira, Wulan Ruhun Natiqoh; Rahmawati, Adinda Putri; Valentina, Martha Nadila; Claudia, Nancy Clara; Bayu, Muhammad Alwino; Prananta, Arie Wahyu (Faculty of Dental Medicine Universitas Airlangga, 2021)
Background: Oral health knowledge, attitudes and behaviors possessed by dental students become provisions in the education and promotion of oral health in the community. Purpose: This study aims to analyze the oral health knowledge, attitudes and behavior of Indonesian dental students in East Java province based on gender and educational stage. Methods: This research is a cross-sectional study using an online questionnaire distributed to dental students at five dental faculties in East Java. 169 respondents in this study completed an online HU-DBI questionnaire with a choice of answers to agree or disagree about the description of oral health knowledge, attitudes, and behavior. Results: Female students have a higher level of knowledge and oral health behavior than the opposite sex with a significance value of <0.001 and 0.05, respectively. There was a significant correlation between knowledge and attitude with a significance level of 0.030 and a correlation between knowledge and behavior with a significant number of 0.037. Conclusion: Female dental students had better oral health knowledge and behavior than male dental students. There is no relationship between the education stage and oral health knowledge, attitudes and behaviour. Further, we found positif association between oral health knowledge and attitudes towards behaviour.